Expansion of the genotypic and phenotypic spectrum of xeroderma pigmentosum in Chinese population. Issue 1 (January 2017) - Zhang, Jia; Cheng, Ruhong; Yu, Xia; Sun, Zhonghui; Li, Ming; Yao, Zhirong
Summary: Background: Xeroderma pigmentosum (XP) is a rare genodermatosis characterized by exaggerated sunburn reactions, freckle‐like pigmentation, and a high possibility of developing cutaneous tumors. XP comprised seven complementation groups (from XP‐A to XP‐G) and a variant form XP‐V. Methods: This study was based on five unrelated Chinese families with six patients clinically suspected to be XP. Mutation screening was performed by direct sequencing of the entire coding region of eight XP genes. Results: All of the pathogenic mutations were identified by mutational analysis, including four novel mutations. Conclusions: Our study successfully identified the pathogenic mutations in six XP patients (three XP‐A, one XP‐G, one XP‐V, and a rare XP‐D group in Chinese population). We reviewed the reported XP cases with mutations in the Chinese population and concluded that four complementation groups (XP‐A, XP‐C, XP‐G, and XP‐V) that occupy the major proportion should be considered as a first step in genetic detection (especially, XPA is the most common group, and unlike in other populations, XP‐G is not rare in the Chinese population). Moreover, XP‐D and XP‐F, two rare subgroups, should also be added for further mutational analysis. Further, we provide some information for Chinese dermatologists that, when an early diagnosis is made, XP‐C and XP‐V patients can have relatively good prognoses.